Anti-Sociale Personality Disorders: Problems Of Theory And Practice - Prostomolotov, Valerii (Psychiatry, Neurology and Medical Psychology, 2017)
The article from the clinical and nosological perspective concerns the «pros and cons» of whether to include dissocial disorder into the classification of personality disorders as the one which is reliably clinically homogeneous. The diversity of dissocial disorder is reasonably justified, with abnormal personality types included in this diversity, and in case of failure of the differential diagnosis and the mentally ill with unexpressed forms of endogenous and exogenous diseases are also included. But in addition, it should be noted that the crimes committed by the so-called normal or accentuated personalities too. The author believes that the common sense and scientific approach should prevail. Despite, for example, the proportion of patients with schizophrenia (we note with its different forms and types of flows) is leading antisocial lifestyle or inclined to commit unlawful acts, isn’t dissocial form of schizophrenia sorted out? The same question can be put in relation to patients with epilepsy, organic brain damage, and others